The Relationship between Facility Conditions and Health Workers' Willingness to Use Electronic Medical Records: A Cross-Sectional Study - Andani, Nurvia; Nurrachmawati, Annisa (GLOBAL HEALTH SCIENCE GROUP, 2024)
Information technology systems have a significant impact on digitalization of health services, to accelerate it the Minister of Health Regulation No. 24/2022 on medical records has been launched. One of the factors for this regulation to work is the availability of human resources who have the intention to switch from conventional medical records to the electronic one. Objective: To determine the relationship between facility conditions and willingness to use electronic medical records at health centers. Methods: A cross-sectional study was conducted on health workers at the Sidomulyo Health Center, Samarinda City, who are tasked with filling out medical records, with a sample size of 48 people taken using the Slovin formula and stratified random sampling technique. The analysis was bivariate analysis with the Chi-Square statistical test and a 95 percent confidence level. Results: respondents who do not have a willingness to use electronic medical records were dominant (58.3%). Bivariat analysis showed that asymp.sig value (0.011). Conclusion: There is a relationship between facility conditions and willingness to use electronic medical records, therefore it suggested to improve required facilities to form willingness of using electronic medical records.